AN ANALYSIS OF POLITENESS STRATEGIES IN ESP ONLINE INTERACTION - Surani, Dewi; Robi, Arief; Septiyani, Rini Dwi; Rohmiyati, Yuli; Hayyin, Fajar (ELTIN Journal, 2025)
Politeness strategies play a crucial role in maintaining social harmony and effective communication, particularly in language learning settings. Some studies have explored the use of politeness strategies in EFL offline classes, emphasizing their role in fostering interaction between students and instructors. However, few studies have focused on online interaction in the context of English for Specific Purposes (ESP) context. This study investigates and analyzes the types and functions of politeness strategies produced by ESP students and a lecturer in online interaction via WhatsApp group. The participants were sophomore accounting students at a private university in Banten. Their use of politeness strategies in requesting assignments, seeking confirmation, and other academic interactions was analyzed using Brown and Levinson’s politeness strategy framework. The results revealed that: (1) positive politeness strategies were most frequently used in the WhatsApp interaction, and (2) these strategies contributed to fostering harmonious relationships and minimizing conflict in online communication. The findings highlight the importance of developing pragmatic awareness in online interaction, and guide future research to investigate politeness in different contexts.